Immunization Services In Rural Population Campaign vs Clinical Approach - Bhardwaj, A K; Gupta, B P; Rana, D D; Swami, H M; Vaidya, N K (Indian Journal of Community Health, 1990)
In the world today, most of our problems can be prevented at community level through change in social behaviour and at a teasonable low cost. To achieve this, we will have to transform available knowledge and technology into action. In 24 hours, app 40000 under-five children die, and out of this, 80'/. can easily be saved through preventive measures (UNICEF, 1989). Immunization, which can alone save 3 million children out of 14 million who die every year, is the most cost-effective programme. During this decade, through determined efforts, the developing countries have been abI e to increase the 'proportion of immunized children from 10./. to 50'/. and are now saving the lives of nearly 1.5 million children annually (UNICEF, 1989). In our rural areas, scattered population and difficult terrain limits the access to the health institutions thus contributing to the low immunization coverage in most parts of our country (Bhargava and Sokhey, 1985). It has been recommended that till such time our primary health care system becomes capable of achieving near universal immunization coverage, a strategy of campaign approach involving different agencies should be adopted (John and Steinhoff, 1981). To prove the value of such programme,an immunization coverage assessment was undertaken in a Rural block in Himachal Pradesh.